The Relevance of CED (Chronic Energy Deficiency) Pregnant Women History with The Growth of Toddlers Aged 2-5 Years in Jelbuk - asri (Fetus : Journal of Midwifery, 2023)
Stunting is a condition of growth failure in toddlers due to chronic malnutrition since the womb. In Jember Regency in 2022, 20.506 from 174,616 toddlers were stunted. With the prevalence of stunting in Jelbuk sub-district 17.55%, and Suko Jember village 155 from 465 toddlers were stunted. One of them is caused by pregnant women with CED and is a risk factor for stunting. Stunting results in decreased physical growth, brain development, intelligence, and the immune system. This study used observational analytic research with a correlational design with a cross sectional approach. Sampling using simple random sampling. From a population of 263 toddlers, a sample of 160 toddlers was obtained. Data collection using secondary data. Data analysis using Chi Square test. Pregnant women who have a history of CED with abnormal growth were 17 respondents (15.5%). Chi Square test results obtained p-value (Asymptotic Significance (2-sided)) is 0.571 > ɑ = 0.05, and OR 0.813. There is no relationship between the history of CED (Chronic Energy Deficiency) of pregnant women and the growth of toddlers aged 2-5 years in Suko Jember Village, Kec. Jelbuk. It is expected that regional midwives detect pregnant women who experience CED early and provide education that the nutritional intake of pregnant women greatly affects the condition of the child who will be born.